KOREOGRAFI PARTISIPATORIS SEBAGAI PRAKTIK PEMULIHAN EKOLOGIS: STUDI KASUS PADA KARYA INDUNG BRAGA BERJAGA - Ferry Cahyo Nugroho; Nurudin; Nur Yasni Robbiulsani (Greget: Jurnal Kreativitas dan Studi Tari, 2025)
This study examines Indung Braga Berjaga as a form of participatory choreography that plays a role in the recovery of ecological and social trauma following the 2024 Cikapundung River flood. The work involved collaboration between Hot Mama Dance Club, Gymnastic Emporium, and the PKK women of Kampung Braga through a community-based creative approach. This research aims to understand how participatory choreography can serve as an ecological recovery practice and strengthen urban social resilience. The study employed a participatory method consisting of direct observation, in-depth interviews with the facilitator and choreographer, and analysis of performance video documentation. The results demonstrate that the creative process was collaborative and reflective, emphasizing the body as a medium for healing and public space as a site for social dialogue. Through movement rooted in lived experiences, the work generated a collective cathartic mechanism and fostered ecological awareness within the community. In conclusion, Indung Braga Berjaga functions not only as an artistic representation of disaster but also as a socio-ecological strategy for community recovery. It is recommended that similar participatory practices be further developed as a model for disaster reflection and resilience building in urban Indonesia.